Providing Quality of Service for Mesh Networks Using Link Delay Measurements - Cordeiro, W.; Aguiar, E.; Moreira, W.; Abelem, A.; Stanton, M. (2007 16th International Conference on Computer Communications and Networks, 2007)
One of the main problems faced by ad hoc networks is providing specific quality of service guarantees for multimedia applications, mainly due to factors such as radio signal fading and node mobility. Since mesh networks are a special type of ad hoc network, they inherit these networks' problems. This paper's main goal is to present OLSR-MD, an extension to OLSR (optimized link state routing), to provide quality of service based on link delay measurements. An evaluation of OLSR-MD in a mesh network to be deployed at the Federal University of Para, by means of ns2 (version 2.30) simulations, showed that this protocol performed better than other OLSR based alternatives studied in the simulations.